Bibliometric mapping of psychological flexibility research: trends and future directions - Wider, Walton; Pang, Nicholas Tze Ping; Lin, Jiaming; Muhammad Ashraf, Fauzi; Jiang, Leilei; Tanucan, Jem Cloyd M. (SAGE Publications Inc., 2024)
In this article, we offer an exhaustive analysis of academic work on psychological flexibility using bibliometric techniques. We identify emerging trends in a dataset of 3535 scholarly articles from the Web of Science database. We highlight key publications, map out the field’s intellectual framework, and anticipate future research avenues through co-citation and co-word analytics. The co-citation assessment revealed five distinct clusters, while the co-word analysis showed three. Although research regarding psychological flexibility has gained recent popularity, there remains a need for more scholarly initiatives to achieve a nuanced understanding of this subject.